Hubungan Literasi Digital Dengan Hasil Belajar Siswa Dalam Pembelajaran Tematik IPS Sekolah Dasar - Suyanti (Jurnal PGSD, 2024)
Digital literacy means increasing knowledge from various sources through computer access, while learning outcomes are the level of academic success of students which includes knowledge, attitudes and even psychomotor in achieving learning objectives in teaching and learning activities. This study aims to reveal the relationship between digital literacy and student learning outcomes in social studies thematic learning. This research is quantitative research with correlation method, the research population is all third grade students, the sampling technique uses Cluster rondom sumpling technique, while data collection uses Tests and research questionnaires. This study concluded that there is a relationship between digital literacy and student learning outcomes in social studies thematic learning for third grade students.